Construction of robust solid electrolyte interface using [Cu(SCN2H4)n]Cl nanowires for stable lithium metal anodes - Lee, Changhyeon; Kim, Subin; Cho, Ki-Yeop; Sim, Kiyeon; Jo, Jinhyeon; Eom, Kwangsup (Elsevier BV, 2024)
Despite the lowest electrode potential (-3.04 V vs. S.H.E) and high capacity (3,860 mAh/g) of lithium metal anodes (LMAs), LMAs face numerous challenges for practical industrialization. In particular, the inevitable lithium (Li) dendrites and volume expansion during the charge/discharge processes cannot be prevented by a naturally formed conventional solid electrolyte interface (SEI), which is not only fragile but also induces the growth of Li dendrites. Herein, we introduce a facile method to artificially construct a robust SEI. Specifically, we form [Cu(SCN2H4)n]Cl nanowires (CTC NWs) precursor on a Cu current collector using electrochemical deposition (ECD) under thiourea (SCN2H4, TU) solution. Then by applying an initial electrochemical reaction of Li deposition/stripping, the CTC NWs are converted into uniform and compact multi-inorganic SEI layers composed of Li2S2/Li2Sx, LiCl, and LixN. Moreover, the residual TU in the CTC NWs promotes favorable LiNO3 decomposition, transforming into Li3N through strong hydrogen bonding (N-H) between both molecules. Such multi-inorganic SEI layers promote homogeneous Li+ flux and significantly decrease the resistance of the SEI, enabling smooth Li plating on the surface. As a result, the LMA employing CTC NWs (Li@CTC NWs) shows exceptional cyclic stability having a low overpotential of 14 mV for more than 1,000 hat a symmetric LMA test at 1 mA cm(-2). Moreover, the Li@CTC NWs parallel to LFP full-cell LMB demonstrates practical improvement by showing about 30 % higher capacity retention (85.6 %) compared to the untreated LMB cell during the initial 140 cycles at 1.0 C-rate.